2012
DOI: 10.1016/j.bpj.2012.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulations of the Cx26 Hemichannel: Insights into Voltage-Dependent Loop-Gating

Abstract: Loop-gating is one of two voltage-dependent mechanisms that regulate the open probability of connexin channels. The loop-gate permeability barrier is formed by a segment of the first extracellular loop (E1) (the parahelix) and appears to be accompanied by straightening of the bend angle between E1 and the first transmembrane domain (TM1). Here, all-atom molecular dynamics simulations are used to identify and characterize interacting van der Waals and electrostatic networks that stabilize the parahelices and TM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 31 publications
1
57
0
Order By: Relevance
“…Nevertheless, the initial events seen in the present simulations indicate that the subsequent rearrangements of the network of electrostatic interactions below D50-K61 are among the steps that enhance the probability of transition to a Ca 2+ -induced closed state. The previously equilibrated Cx26 hemichannel and other connexin structural models also associate these residues with electrostatic interactions in the open conformation (21,22).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Nevertheless, the initial events seen in the present simulations indicate that the subsequent rearrangements of the network of electrostatic interactions below D50-K61 are among the steps that enhance the probability of transition to a Ca 2+ -induced closed state. The previously equilibrated Cx26 hemichannel and other connexin structural models also associate these residues with electrostatic interactions in the open conformation (21,22).…”
Section: Discussionmentioning
confidence: 85%
“…Several charged residues in this region (D46, E47, D50, K61, R75, R184) participate in electrostatic networks (21). Those that are negatively charged are pore-lining, which may favor accumulation of permeant cations in this region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When sufficient E2-E2 hydrogen bonds ($4 per pair or $24 per gap junction channel) had been formed, the two hemichannels would be docked properly and ready to 'open' as a functional gap junction channel. The open transition probably requires further conformational change at the E1 domains, part of which could be the previously described 'loop-gating' process (Kwon et al, 2012). Our earlier structural studies Nakagawa et al, 2011) indicated that the inter E1-E1 hydrogen bonds in Cx26 and/or Cx32 channels are also formed and might help to stabilize the gap junction channel, but they are unlikely to serve for docking recognition because the hydrogen-bond-forming residues are almost identical for both compatible and non-compatible groups of Cxs.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, mutations in this residue (or its homologous residue at position 76) have been associated with at least four different human disorders. Furthermore, the crystal structure of Cx26, a connexin closely related to Cx32, shows that the Arg 75 residue to be a key component of an electrostatic cluster having a central role in interprotomeric interactions of the Cx26 hemichannel (23,31). These facts suggest that the arginine at position 75 is critical for the normal functioning of Cx32.…”
Section: Alterations In the Voltage Dependence Of Gating Can Account mentioning
confidence: 99%